An emotion analysis in learning environment based on theme-specified drawing by convolutional neural network - He, Tiancheng; Li, Chao; Wang, Jiayang; Wang, Minjun; Wang, Zhenghao; Jiao, Changyong (Frontiers in Public Health, 2022)
Emotion in the learning process can directly influence the learner’s attention, memory, and cognitive activities. Several literatures indicate that hand-drawn painting could reflect the learner’s emotional status. But, such an evaluation of emotional status, manually conducted by the psychologist, is usually subjective and inefficient for clinical practice. To address the issues of subjectivity and inefficiency in the painting based emotional analysis, we conducted an exploration of a painting based emotional analysis in learning environment by using convolutional neural network model. A painting image of 100×100 pixels was used as input for the model. The instant emotional statue of the learner was collected by filling out a questionnaire and was reviewed by a psychologist and then used as the label for training the convolutional neural network model. With the completion of convolutional, full-connected, and classification operations, the features of the painting image were learned from the underlying pixel matrix to the high-level semantic feature mapping. Then the emotional classification of the painting image could be made to reflect the learner's emotional status. Finally, the classification result by the model was compared with the result manually conducted by a psychologist to validate the model accuracy. We conducted an experiment in a university at Hangzhou, and 2103 learners joined in the experiment. The learner was required to first fill out a questionnaire reporting emotional status in the learning process, and then to complete a theme-specified painting. 2000 valid paintings were received and divided into training dataset (1600) and test dataset (400). The experimental result indicated that the model achieved the accuracy of 72.1%, which confirmed the effectiveness of the model for emotional analysis.